Students’ Respond Through CAKE Application in Learning English Pronunciation Skill - Rinata, I Gede Wila Selamat (STKIP Agama Hindu Singaraja, 2024)
In today's digital age, many students still face challenges in learning, particularly in mastering spoken English. Despite this, there's a plethora of tools available to support educational needs. Students now have access to knowledge not only through traditional books but also via smartphones, with AI-based apps emerging as a popular option in the educational landscape. This study aims to gauge student response to using the Cake AI-based application to enhance their speaking skills. Employing a mixed-method approach, the research utilized observation via the triple E rubric and interviews as data collection instruments. Participants included grade 11 students from SMA N 1 Kubutambahan. Findings suggest that this application effectively boosts student motivation and improves their speaking abilities.